2021
DOI: 10.1088/1674-1056/abeedb
|View full text |Cite
|
Sign up to set email alerts
|

A comparative study of the self-propelled jumping capabilities of coalesced droplets on RTV surfaces and superhydrophobic surfaces

Abstract: Understanding the mechanism of coalescence-induced self-propelled jumping behavior provides distinct insights in designing and optimizing functional coatings with self-cleaning and anti-icing properties. However, to date self-propelled jumping phenomenon has only been observed and studied on superhydrophobic surfaces, other than those hydrophobic surfaces with weaker but fairish water-repellency, for instance, vulcanized silicon rubber (RTV) coatings. In this work, from the perspective of thermodynamic-based e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 33 publications
0
4
0
Order By: Relevance
“…The present study deepens the physical mechanism behind the wetting behavior, which would have implications in the actual fabrication of novel material for water treatment, surface catalysis and self-cleaning of surfaces. [44,45]…”
Section: Discussionmentioning
confidence: 99%
“…The present study deepens the physical mechanism behind the wetting behavior, which would have implications in the actual fabrication of novel material for water treatment, surface catalysis and self-cleaning of surfaces. [44,45]…”
Section: Discussionmentioning
confidence: 99%
“…Regarding superhydrophobic surface study [18], where water self-propels to coalesce droplets and jump off the surface. Since the contact angle of RTV surface is smaller than that of the superhydrophobic surface, this phenomenon does not occur on the RTV surface.…”
Section: Superhydrophobic Surfacementioning
confidence: 99%
“…Since the contact angle of RTV surface is smaller than that of the superhydrophobic surface, this phenomenon does not occur on the RTV surface. Their mechanism is described in Figure 6 [18]. The reason of this phenomenon is that the roughness of the material surface is different and causes different contact modes, as shown in Figure 7 [16].…”
Section: Superhydrophobic Surfacementioning
confidence: 99%
“…The surface polarity and free energy of solids are vital indicators influencing a droplet’s nucleation efficiency during water harvesting [ 6 , 7 , 8 , 9 , 10 ]. Wang et al [ 11 ] found that the wettability of different surfaces was due to droplets sliding with different rhythms. Pogorzelski et al [ 12 , 13 ] suggested that clean metal surfaces have a higher surface tension and hydrophilicity, which can improve the heat exchange efficiency between water vapor and solid surfaces.…”
Section: Introductionmentioning
confidence: 99%